PENYELESAIAN WANPRESTASI PERJANJIAN LISAN KERJASAMA RENTAL ALAT BERAT ANTARA KREDITUR DAN DEBITUR - Sri Indah Lestari A.S; Hayatul Ismi; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Article 1313 of the Civil Code provides the formulation of "a contract oragreement, an agreement is an act by which one or more people bind themselvesto one or more other people." The occurrence of a default between the creditorand the debtor in the heavy equipment rental cooperation agreement which iscarried out verbally in which in the agreement the creditor must provide a heavyequipment to the debtor to be rented out to a third party, providing profit sharingfrom the existing heavy equipment rental. The purpose of this study is first, todetermine the cause of the occurrence of default in the verbal agreement ofcreditors and debtors in heavy equipment rental cooperation. Second, to find outthe efforts to resolve the default of the verbal agreement on the rental agreementbetween the creditor and the debtor.This type of research is a sociological research, because the authordirectly conducts research on the location of the place being studied in order toprovide a complete and clear picture of the problem under study.The results of the research and discussion show that first, the occurrenceof default between creditors and debtors in the heavy equipment rentalcooperation agreement which is a default or breach of promise and a statement ofnegligence in accordance with Article 1238 of the Civil Code. Second, how tosolve the problem by using a subpoena, negotiation and also a lawsuit filed at theDistrict Court. Third, the result of the lawsuit filed is stipulating that the debtorhas defaulted so that he is punished to compensate for the losses suffered by thecreditor. In the heavy equipment rental cooperation agreement between creditorsand debtors, there should be a written agreement not just a statement and moreemphasis on articles related to how to calculate the distribution of profits fromheavy equipment rental and further clarify what are the rights and obligations ofeach of the creditors and debtor. So that the creditors or those who provide heavyequipment for rental are more assertive in carrying out the contents of theagreement and taking action against debtors who violate the agreement inaccordance with the law and apply a comprehensive compensation system. Inorder to provide a deterrent effect for debtors who commit acts against the law.Keywords: Oral agreement- leasing- Not carrying out the agreement